Correlation between Serum Ferritin and Cardiac Troponin I in Major Beta Thalassemia Children - Muhammad Ali Shodikin; Renny Suwarniaty; Susanto Nugroho (Journal of Tropical Life Science, 2016)
Background: Major beta thalassemia (MBT) is a hereditary disease which synthesis defect on beta chains of haemoglobin, it is cause red blood cell destruction and the symptoms of anemia. Red blood cells destruction, frequent blood transfusion and low adherence to routine use of iron chelator were cause iron accumulation in the heart, liver and endocrine organs. Accumulation of iron in the myocard can lead acute myocardial infarction. One of cardiac markers that had been used for the diagnosis of myocardial infarction was cardiac troponin I (cTnI). The aim of this research is find correlation between serum ferritin levels and cTnI in MBT children.Methods: A descriptive analytic research was conducted using a cross sectional design. The subjects were divided into 2 groups, the MBT group and the control group. In both groups perform laboratory examination to checks the serum ferritin and cTnI levels. Data were analyzed using t-test and Pearson correlation test.Result: Eleven children in the MBT group and 11 children in the control group were involved in this study. In the MBT group, the mean of serum ferritin and cTnI levels were 4292.5 Î¼g/L and 0.22 ng/mL respectively. In the control group, the mean of serum ferritin and cTnI levels were 136.2 Î¼g/L and 0.20 ng/mL respectively. The mean of serum ferritin levels in MBT group was higher than control, statistically significant (p= 0,0004 ). The mean of serum cTnI in MBT group was higher than control, statistically not significant (p= 0,82). In MBT group, there was a weak corellation between serum ferritin and cTnI levels (r = 0,34).Â Keywords: Major beta thalassemia, children, ferritin, cTnI